Low incidence of seizures in patients with chronic subdural haematoma. Issue 11 (November 1993) - Ohno, K; Maehara, T; Ichimura, K; Suzuki, R; Hirakawa, K; Monma, S
Abstract : A total of 129 patients treated for chronic subdural haematoma were studied retrospectively to evaluate the incidence of seizures. None of 73 patients who were given prophylactic antiepileptic drug treatment developed seizures. Only two of 56 patients not given prophylaxis, developed early postoperative seizures. In these two, surgical technique was thought to be responsible. One patient developed complex partial seizures preoperatively. The incidence of seizures was therefore low, and similar to that previously reported for minor head injury. This study suggests that routine use of antiepileptic prophylaxis is not justified in patients with chronic subdural haematoma caused by minor head injuries, or other causes when there are no additional lesions present on CT scans.